2009
DOI: 10.1177/0013916509333509
|View full text |Cite
|
Sign up to set email alerts
|

Crowding and Cognitive Development

Abstract: Residential crowding in both U.S. and U.K. samples of 36-month-old children is related concurrently to the Bracken scale, a standard index of early cognitive development skills including letter and color identification, shape recognition, and elementary numeric comprehension. In the U.S. sample, these effects also replicate prospectively. Statistical controls for income, child gender, maternal age, and maternal education are incorporated throughout. In both samples the association between crowding and cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 26 publications
0
19
1
Order By: Relevance
“…The home environment encompasses both relational factors such as the quality of parenting, including maternal warmth, sensitivity, and responsivity toward the child, as well as material factors such as family organization and the availability of resources and learning materials. The home environment is an important predictor of child development and may account for differences in children’s outcomes [48]. The quality of the home environment is often poorer in low socioeconomic status (SES) families [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…The home environment encompasses both relational factors such as the quality of parenting, including maternal warmth, sensitivity, and responsivity toward the child, as well as material factors such as family organization and the availability of resources and learning materials. The home environment is an important predictor of child development and may account for differences in children’s outcomes [48]. The quality of the home environment is often poorer in low socioeconomic status (SES) families [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the home learning environment is more strongly associated with a child's cognitive development than a child's preschool or kindergarten environment (Anders et al, 2012). However, a less stimulating home learning environment can contribute to cognitive deficits, impair language acquisition, and delay school readiness by age three years (Evans et al, 2010;Trentacosta et al, 2008;Vernon-Feagans, Garrett-Peters, Willoughby, Mills-Koonce, & Investigators, 2012). Long-term consequences include lower academic achievement, less likelihood of employment, and lower earnings (Pungello et al, 2010;Pungello, Iruka, Dotterer, Mills-Koonce, & Reznick, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In our study group, we found that those with multiple siblings had more developmental delay. Similarly, there are studies supporting the negative effects of crowded families on cognitive development [29, 30]. The delay in gross motor skills was higher in children with low maternal education levels.…”
Section: Discussion/conclusionmentioning
confidence: 81%